(untitled) (Bulletin of the International Association for Paleodontology, 2025)
Forensic odontology is crucial for identifying individuals, particularly in cases of mass disasters and criminal investigations, where age estimation aids in reconstructing biological profiles of unidentified remains. Teeth are favored for age estimation due to their exceptional durability and resistance to heat, chemicals, decay, and various other factors. As teeth have a unique and durable structure, they serve as a reliable indicator for age estimation. Various methods can be used in age estimation on clinical, radiographic, and biological dental examinations. Visual methods are based on the tooth eruption and morphological parameter of aging, like attrition, deposition of secondary dentin, and discoloration. Radiographic method can be used with various analysis methods such as Schour and Massler, Adisty Atlas, modified Gleiser and Hunt, Demirjian scoring, Al-Qahtani method, Camerier, and crown and root formation stages with modified Moores method to provide valuable insights into the stages of tooth development. Additionally, DNA methylation offers a molecular approach with age-specific patterns. Complementary biological methods, such as telomere length measurement and secondary dentin analysis, further contribute to the accuracy of age assessments. Artificial intelligence (AI) has also been widely used especially in virtual autopsy in identifying a person based on age estimation. By integrating these diverse methodologies, forensic odontology can significantly improve the reliability of age estimations, providing critical information for legal and medical applications in the identification of both living and deceased individuals. This review emphasizes the importance of a multidisciplinary approach in advancing forensic odontology and enhancing age estimation techniques. Keyword : Age Estimation; DNA Methylation; Forensic Odontology